Thermal Treatment of γ-Al2O3 for the Preparation of Stereolithography 3D Printing Ceramic Slurries - Li, He; Liu, Yongsheng; Liu, Yansong; Zeng, Qingfeng; Liang, Jingjing (Frontiers in Materials, 2019)
Alumina (Al2O3) suspensions were prepared for the effective application in the stereolithography three-dimensional (3D) printing process. Thermal treatment of -Al2O3 could optimize the ceramic slurries to meet the requirements of stereolithography 3D printing technique. In this study, alumina powders were modified by thermal treatment at different temperatures for the preparation of well dispersed ceramic slurries. The influence of thermal treatment on the raw powder, printed green bodies, and sintered alumina parts was systematically studied. Thermogravimetric analysis indicated that the decomposition temperature of photosensitive resin was between 390C and 460C. The alumina powders became denser, the crystal grains changed from round sphere-shaped to long cylinder-shaped, and the pores disappeared with increasing thermal treatment temperature. After the 3D printing process, the microstructure of green bodies and sintered alumina ceramics exhibited significant variation. Decomposition and removal of photosensitive resin led to higher water absorption, higher porosity, and lower bulk density of alumina ceramics compared to the printed green bodies. The scattering phenomenon in ceramic slurries and layer-by-layer forming characteristic determined the different shrinkage in three directions. Experimental results suggested that 1500C was considered as the optimal thermal treatment temperature, with the water absorption of 107%, open porosity of 91%, and bulk density of 0.67g·cm3. The higher thermal treatment temperatures would cause alumina powders to clump and agglomerate.